Insights into the mechanism of binding of doxorubicin and a chlorin compound with 22-mer c-Myc G quadruplex - Shukla, Aishwarya; Kumari, Soni; Sankar, Muniappan; Nair, Maya S. (Biochimica et biophysica acta. General subjects, 2023)
The interaction of small molecules with G quadruplexes is in focus due to its role in molecular recognition and therapeutic drug design. Stabilization of G-quadruplex structures in the promoter regions of oncogenes by small molecule binding has been demonstrated as a potential approach for cancer therapy. In this study, electronic spectroscopy (ultraviolet-visible, fluorescence, circular dichroism), differential scanning calorimetry, and molecular modeling were employed to explore the interactions between the chemotherapy drug doxorubicin and a chlorin compound 5,10,15,20-tetraphenyl-[2,3]-[bis(carboxy)-methano]chlorin (H2TPC(DAC)), and the c-Myc 22-mer G quadruplex DNA. Spectroscopic studies indicated external binding of the compounds with partial stacking at the end quartets. Calorimetric studies and temperature dependent circular dichroism data displayed increased melting temperatures of G quadruplex structure on binding with the compounds. Circular dichroism spectra indicated that the G quadruplex structure is intact upon ligand binding. Both the compounds showed binding affinities of the order of 106 M−1. Fluorescence lifetime studies revealed static quenching as major mechanism for fluorescence quenching. Polymerase chain reaction stop assay hinted that binding of both ligands under study could inhibit the amplification of the DNA sequence. Results show that doxorubicin and H2TPC(DAC) bind to the 22-mer c-Myc quadruplex structure with good affinity and induce stability. Doxorubicin and H2TPC(DAC) have demonstrated their affinity towards c-Myc G quadruplex DNA, stabilizing it and inhibiting expression and polymerization. The results can be of practical use in designing new analogs for the two compounds, which can become potent anti-cancer agents targeting the c-Myc GQ structure. [Display omitted] •c-Myc GQ DNA interacts with Doxorubicin and a novel Chlorin (H2DAC) compound with high affinity•Ligand binding induced thermal stability.•Fluorescence lifetimes confirm the static quenching of ligand fluorescence.•Ligands's binding could inhibit the amplification of the DNA sequence.•Chlorins can be a new class of GQ-targeting compounds.